2018
DOI: 10.5830/cvja-2017-038
|View full text |Cite
|
Sign up to set email alerts
|

Short-term rehospitalisation or death and determinants after admission for acute heart failure in a cohort of African patients in Port Harcourt, southern Nigeria

Abstract: SummaryBackgroundHeart failure (HF) is a major health burden globally and contributes significantly to morbidity and mortality related to cardiovascular disease. The aim of this study was to determine the outcome, and factors determining these outcomes in patients admitted for acute HF and followed up for six months.MethodsThis was a hospital-based, prospective study. Subjects included consecutive patients with a confirmed diagnosis of acute HF admitted to the medical wards of the University of Port Harcourt T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
(36 reference statements)
3
3
1
Order By: Relevance
“…The relatively young age found in our cohort is in agreement with the vast majority of studies carried out in SSA [4,10,[12][13][14][15][16][17][18][19][20][21] (Table 3), it contrasts, however with the situation in European countries, North America, and Japan, where HF is essentially a problem of the elderly (mean age at presentation 72 years) [22]. As highlighted by several authors, the younger patients with AHF in ASS may be related to the etiology of HF.…”
Section: Clinical Profile and Risk Factorssupporting
confidence: 92%
See 1 more Smart Citation
“…The relatively young age found in our cohort is in agreement with the vast majority of studies carried out in SSA [4,10,[12][13][14][15][16][17][18][19][20][21] (Table 3), it contrasts, however with the situation in European countries, North America, and Japan, where HF is essentially a problem of the elderly (mean age at presentation 72 years) [22]. As highlighted by several authors, the younger patients with AHF in ASS may be related to the etiology of HF.…”
Section: Clinical Profile and Risk Factorssupporting
confidence: 92%
“…Rheumatic heart diseases and cardiomyopathies are essentially problems of youth and middle-aged individuals. Furthermore, hypertension is known to occur early in Africans and African Americans, with greater adverse consequences [4,5,22,23] The higher rate of HF in women found in the present study is consistent with that found in about half of the studies conducted in SSA [4,10,12,13,15,16,[19][20][21][24][25][26][27][28][29][30][31][32] (Table 3). Reported sex differences in different SSA regions may be related to patient selection, the burden of cardiovascular risk factors, and regional etiologic variations.…”
Section: Clinical Profile and Risk Factorssupporting
confidence: 90%
“…Leg swelling is a marker of volume overload and is associated with severe symptoms and poor outcomes in HF, which may explain why leg swelling is a positive predictor of mortality in HF patients in Tanzania and elsewhere [ 39 , 40 ]. Other studies have found age and NYHA class to be predictors of mortality in HF patients in SSA, although they were not predictive of mortality in our cohort [ 41 43 ]. Age and NYHA may not have been significant predictors of mortality in our study due to our relatively small sample size, our relatively short follow-up period examining thirty-day mortality, and the relatively larger impact of other factors such as engagement with the healthcare system in our setting.…”
Section: Discussioncontrasting
confidence: 80%
“…In our study, 52.9% of HF patients with readmission had NYHA class III. In other settings, the predominant NYHA grade were as follows: in the US, 67% had NYHA class II [21]; in Nigeria, 52.2% were class III [23]; in Ethiopia 73.6% were class IV [27]; and prior research in Tanzania found that 34.0% were class IV [28]. is shows that HF patients in developing countries present to health centres with later-stage symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…is study found that among all HF admissions, 38.5% were readmissions. Studies in the United States (US) have shown readmission rates for HF ranging from 14.2% to 30% [18][19][20][21], whereas studies in Uganda and Nigeria reported readmission rates of 31.4% and 35.6%, respectively [22,23]. e higher readmission rates observed in African settings could be due to difference in health care and number of health care personnel.…”
Section: Discussionmentioning
confidence: 99%